2018
DOI: 10.1515/pjfns-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Specific Detection of Escherichia coli O157:H7 in Ground Beef Using Immunomagnetic Separation Combined with Loop-Mediated Isothermal Amplification

Abstract: Escherichia coli O157:H7 is well known for many foodborne outbreaks that lead to fatal infections in human being worldwide. The objective of this study was to develop a rapid and sensitive method for detection of EHEC O157:H7 from ground beef using a method that combined immunomagnetic separation (IMS) with loop-mediated isothermal amplifi cation (LAMP). The EHEC O157:H7 cells were separated with Dynabeads coated with anti-EHEC O157:H7 after a short enrichment for 4 h. Then, EHEC O157:H7 was identifi ed by LAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Qin et al ( 2018 ) established a rapid and specific detection of Escherichia coli O157: H7 in ground beef using IMS-LAMP. The LAMP method results analyzed with real-time turbidity measurements showed high specificity and sensitivity, with a positive detection rate of amplification of EHEC O157: H7 DNA diluted to a minimum equivalent concentration of 1.8 × 10 1 CFU/ml, which was 10 times more sensitive than the conventional PCR assay.…”
Section: Lamp In Food Microbial Detectionmentioning
confidence: 99%
“…Qin et al ( 2018 ) established a rapid and specific detection of Escherichia coli O157: H7 in ground beef using IMS-LAMP. The LAMP method results analyzed with real-time turbidity measurements showed high specificity and sensitivity, with a positive detection rate of amplification of EHEC O157: H7 DNA diluted to a minimum equivalent concentration of 1.8 × 10 1 CFU/ml, which was 10 times more sensitive than the conventional PCR assay.…”
Section: Lamp In Food Microbial Detectionmentioning
confidence: 99%
“…Ground beef contaminated with 3 × 10 1 CFU/mL of E coli O157:H7 could also be detected by IMS‐LAMP assay. With the help of IMS, the interference of food ingredients was reduced and the detection sensitivity was improved (Qin et al., 2018). EDC/NHS‐activated MPs decorated with polyclonal antibody were used to preconcentrate cells.…”
Section: The Application Of Ims In Food Microorganisms Detectionmentioning
confidence: 99%
“…Similar to our study; Weagant et al (2011) reported that 0.1-0.3 cfu E. coli/g in artificially inoculated alfalfa sprouts gave an amplification signal when if OMS method used only after a 5-h enrichment time. According to the results of another study done with OMS followed by loop-mediated isothermal amplification (LAMP), the combined assay captured and detected a bacterial concentration as low as 3×10 1 cfu/mL from the meat samples within a 6-h total analysis time when if a 4-h short pre-enrichment was applied (Qin et al, 2018). On the contrary; Fu et al (2005), who firstly combined OMS and RTiPCR for detection of EHEC, found the minimum detection limit of OMS-RTiPCR combined assay as < 5×10 2 cells/mL for EHEC suspensions in buffer and as 1.3×10 4 cells/g in ground beef without using any enrichment step within an 8-h total analysis time.…”
Section: Detection Of Ehec In Artificially Contaminated Raw Milk and mentioning
confidence: 99%
“…Escherichia coli O157:H7 (EHEC) which is an enterohemorrhagic serotype of the Shiga toxin-producing E. coli (STEC), is considered a serious public health problem since it is recognized as a major pathogen of foodborne diseases in humans with a capable of causing diseases like diarrhea, hemorrhagic colitis (HC), the potentially fatal hemolytic uremic syndrome (HUS), thrombotic thrombocytopenic purpura (TTP), and kidney failure (Qin et al, 2018;Jaakkonen et al, 2017). Despite the wide-scale distribution of EHEC in all types of foods, it is primarily transmitted through cattle and so raw or undercooked minced or ground beef (Centers for Disease Control and Prevention, 1997;King et al, 2014;Xiong et al, 2014), but milk and dairy products including especially raw or inadequately pasteurized milk (Kumar et al, 2013;Goh et al, 2002;Allerberger et al, 2001), yoghurt (Morgan et al, 1993), and raw-milk cheeses (Gaulin et al, 2012;Honish et al, 2005) have also been highly susceptible to contamination by EHEC.…”
Section: Introductionmentioning
confidence: 99%